2013
DOI: 10.1103/physreve.88.042901
|View full text |Cite
|
Sign up to set email alerts
|

Loss of stability of a solitary wave through exciting a cnoidal wave on a Fermi-Pasta-Ulam ring

Abstract: The spatiotemporal propagation behavior of a solitary wave is investigated on a Fermi-Pasta-Ulam ring. We observe the emergence of a cnoidal wave excited by the solitary wave. The cnoidal wave may coexist with the solitary wave for a long time associated with the periodic exchange of energy between these two nonlinear waves. The module of the cnoidal wave, which is considered as an indicator of the nonlinearity, is found to oscillate with the same period of the energy exchange. After the stage of coexistence, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…This leads the deviation from the fitted curve of Eq. (17). So with the increase of energy, the nonlinear part in the interaction potential of Eq.…”
Section: Transition From Solitons To Solitary Waves In the Fpu Latticementioning
confidence: 97%
See 3 more Smart Citations
“…This leads the deviation from the fitted curve of Eq. (17). So with the increase of energy, the nonlinear part in the interaction potential of Eq.…”
Section: Transition From Solitons To Solitary Waves In the Fpu Latticementioning
confidence: 97%
“…The velocity v and energy E of the solitary wave are calculated numerically: v = 1.000743, E = 0.044664, and v and E satisfy the relation of Eq. (17). Then the solitary wave may be a soliton solution.…”
Section: Transition From Solitons To Solitary Waves In the Fpu Latticementioning
confidence: 99%
See 2 more Smart Citations
“…Kartashov et al [22,23] reported, respectively, that in contradistinction with the case of localized solitons (where the spectrum of perturbations is discrete) for cnoidal waves, one has a band of possible increments at each energy flow, and, under the proper conditions of low-and high-energy flows, the two-dimensional cnoidal waves appear to be robust enough to be observable in experiments. Recently, Yuan et al [24] demonstrated that, due to the interaction of the cnoidal wave with the solitary wave, phonons can be radiated, which destroys the cnoidal wave and finally results in a loss of stability of the solitary wave. However, the basic features (amplitude and width) of cnoidal waves in a dense relativistic degenerate magnetoplasma consisting of relativistic degenerate electrons and nondegenerate cold ions is still lacking.…”
Section: Introductionmentioning
confidence: 99%